New bioconjugation strategies for selective Cysteine functionalization - Silva, Maria J. S. A. (2022)
The quest for novel aqueous chemical strategies that allow chemo-, regio- and site-selective modifications of native biomolecules beought about major insights into basic biology and enabled the development of functional bioconjugates with unprecedented properties. The success of these bioconjugates is prominent in many applications of life science research allowing to precisely study molecular interactions relevant for the normal operation of biomolecules and uncovering their typical properties and functions within important biological processes. Besides this, chemoselective modifications made great contributions in the pharmaceutical field, opening several opportunities for the development of advanced targeted therapies. To deliver on these promises, bioconjugation strategies must allow easy access to well-defined constructs under biocompatible conditions that include low to room temperatures, mild stirring and aqueous buffered solvent at near physiological pH. Diverse Michael acceptors have been described to promote site-selective modifications on cysteine residues in peptides and native proteins giving great contributions to the design of novel advanced therapeutic and diagnostic tools. Herein, novel activated Michael acceptors have been extensively investigated for the selective modification o N-terminal cysteines either through ortho-boronic acid activation or N-Hydroxysuccinimide (NHS)-activation of acrylamides that enable a subsequent intramolecular amidation. In particular, NHS-activated acrylamides exhibited remarkable selectivity and versatility for amino-sulfhydryl stapling not only in N-terminal cysteines but also for the cross-linking of a cysteine to a nearby lysine residue under fine-tuned reaction conditions. The great control displayed by these reagents and the observed compatibility with other bioconjugation handles further allowed the dual site-selective functionalization of unprotected peptides. Finally, this approach was applied for the functionalization of bombesin peptide with a promising Ru(II) polypyridyl complex for targeted photodynamic therapy. As a targeting unit, bombesin conjugates are internalized in cells overexpressing gastrin releasing peptide receptors, that are commonly associated with diverse cancer types. The superior selectivity and high phototoxicity of the synthesized Ru(II) complex-bombesin conjugates are shown.